Ace of shades - Foody, Amanda (Foody, Amanda. Shadow Game series, 2018)
New Reynes -- the City of Sin -- is no place for a proper young lady like Enne, who had to leave finishing school early to pursue her missing mother with only one name as a clue. When she finds Levi Glaisyer, however, he is not a proper gentleman but a street lord and con man who brings his own troubles and enemies to tangle with hers and catch them both in a dangerous gamble that could mean their lives.